Utilization of Organic Waste for Alternative Energy: Socialization and Education in Community Service Programs - Hasan Harun, Ervan; Lihawa, Fitryane (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Pengelolaan sampah, khususnya sampah organik, menjadi tantangan serius di Indonesia, dengan sekitar 60-70% dari total sampah rumah tangga terdiri dari limbah organik. Pemanfaatan sampah organik sebagai sumber energi alternatif, melalui teknologi seperti biogas dan biodiesel, dapat mengurangi volume sampah dan ketergantungan pada bahan bakar fosil. Kegiatan sosialisasi yang dilaksanakan di Desa Suka Damai bertujuan meningkatkan kesadaran masyarakat tentang pengelolaan sampah organik dan penerapan teknologi sederhana seperti biodigester. Melalui workshop, demonstrasi, dan diskusi, peserta diajarkan cara mengolah sampah organik menjadi biogas. Evaluasi menunjukkan peningkatan pemahaman peserta dari 9% menjadi 92% setelah mengikuti kegiatan sosialisasi. Program ini diharapkan tidak hanya mengurangi dampak negatif lingkungan, tetapi juga meningkatkan kemandirian energi di tingkat lokal, serta memanfaatkan sumber daya yang tersedia secara melimpah, yaitu sampah organik. Waste management, especially organic waste, is a serious challenge in Indonesia, with around 60-70% of total household waste made up of organic waste. The use of organic waste as an alternative energy source, through technologies such as biogas and biodiesel, can reduce the volume of waste and dependence on fossil fuels. The socialization activities carried out in Suka Damai Village aim to increase public awareness about organic waste management and the application of simple technologies such as biodigesters. Through workshops, demonstrations, and discussions, participants were taught how to process organic waste into biogas. The evaluation showed an increase in participants' understanding from 9% to 92% after participating in socialization activities. This program is expected not only to reduce negative environmental impacts, but also to increase energy independence at the local level, as well as to utilize the abundant resources available, namely organic waste.